Beyond Sovereignty
VIII, 250 p.
Keywords: Explores the central role of the British Empire in developing transnational ideas, institutions and social movements of increasing scope and influence in the eras of high imperialism and the two world wars. Chapters follow transnational dynamics and debates over sovereignty in the domains of sexuality, law, politics, culture and religion.